Grammatical Error of EFL Senior High School Learners in Writing: A Review of Language Interference Studies - Vidya Mandarani (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2020)
Considering the importance of English as one of pivotal courses in compulsory education, Indonesian students are liable to error produced during their language acquisition phase. This paper’s aim is to unveil what is the most frequent language interference presents in students’ writing that centered upon grammatical context, along with its correlative factors and the very process of interference, encountered by senior high school learners within their second or foreign language acquisition phase. This was carried through library research, which relies towards other articles from researchers, under the same concerns of language interference, as the main objective. There are 4 researches taken as primary sources that issued or published within the last 5 years. The findings of each studies are assessed in gaining a better insight for this paper’s inquiries. From the analysis, the outcomes proved that the errors mostly occurred were caused by interference came in a form of incorrect use of verb as well as copula ‘be’ omission during sentence composing. Such errors were not solely caused by the entity of language interference alone, yet also compounded by the lack of motivation in using English as a communication medium both inside and outside the classroom activity.